ORLA combined with telerehabilitation in patients with subacute Poststroke aphasia: a randomized controlled trial - Li Gan; Litao Huang; Lijuan Li; Xin Yang; Lijiao Meng; Zijian Pang; Quan Wei (Scientific Reports)
Abstract Oral reading for language in aphasia (ORLA) therapy coupled with telerehabilitation (TR) is a promising adjunct to treatment for aphasia. This single-center, randomized, single-blind, 6-month trial aimed to evaluate whether ORLA combined with TR demonstrates comparable efficacy to conventional ORLA offline rehabilitation for improving comprehensive language ability in subacute aphasia patients while assessing longitudinal treatment effects. Enrolled patients were randomized 1:1:1 into Group A (medium–high intensity ORLA TR), Group B (low-intensity ORLA TR), and Group C (medium–high intensity ORLA offline). All groups received a 6-month, 90-h intervention comprising three treatment phases. The primary outcome was a change in Aphasia Quotient (AQ) at baseline and 4 weeks, 3 months, and 6 months post-treatment. The secondary outcomes included quality of life and language subscale scores at the same time points. A total of 42 participants were analyzed, Group A demonstrated a non-significant mean difference of − 0.62 (95% CI − 5.00 to 6.23; P = 0.825) in AQ compared to Group C. A statistically significant difference in the Stroke Aphasia Quality of Life-39 Scale (SAQOL-39) scores between Group A and Group C (mean difference: − 8.19; 95% CI [− 12.39, − 3.99]; P < 0.001). Group A vs. Group C: No statistically significant differences were observed in any of the aforementioned language subskills between Group A and Group C (P > 0.05 for all comparisons). ORLA combined with TR demonstrated comparable efficacy to conventional ORLA offline rehabilitation, serving as a viable alternative for home-based speech rehabilitation in subacute aphasia patients. This TR approach improved both comprehensive language ability and quality of life, with sustained treatment effects over time. First registration date: August 18, 2023 (retrospective registration, Chinese Clinical Trial Registry number: ChiCTR2300074870).